2017
DOI: 10.18666/jorel-2017-v9-i4-8653
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy of Risk Taking in Outdoor Recreation as a Predictor of the Self-Efficacy of Risk Taking in Essay Writing

Abstract: During two decades of teaching, we have observed that writing students seem more emotionally honest when their writing class is accompanied by an outdoor recreation component. The ability to take perceived risks is important to both outdoor recreation and writing; thus, we postulated that confidence gained in taking risks in outdoor experiences might affect students' confidence in taking risks in their reflective writing. In this study, we applied Bandura's (1997) self-efficacy theory to two classes of writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…Several studies have indeed found that success in one area may lead to enhanced PSE in another (e.g. Samuels & Gibb, 2002;Taniguchi et al, 2017;Widmer et al, 2014). In one study involving students aged 17-23, researchers examined the impact of outdoor risk-taking (Taniguchi et al, 2017).…”
Section: Solicited Me Recall and The "Spreading" Of Psementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indeed found that success in one area may lead to enhanced PSE in another (e.g. Samuels & Gibb, 2002;Taniguchi et al, 2017;Widmer et al, 2014). In one study involving students aged 17-23, researchers examined the impact of outdoor risk-taking (Taniguchi et al, 2017).…”
Section: Solicited Me Recall and The "Spreading" Of Psementioning
confidence: 99%
“…Samuels & Gibb, 2002;Taniguchi et al, 2017;Widmer et al, 2014). In one study involving students aged 17-23, researchers examined the impact of outdoor risk-taking (Taniguchi et al, 2017). Perhaps unsurprisingly, participation in outdoor activities enhanced PSE for outdoor risk-taking.…”
Section: Solicited Me Recall and The "Spreading" Of Psementioning
confidence: 99%
See 1 more Smart Citation
“…Çünkü artan beceri seviyesi uzmanlık, güven veya öz-yeterliliğin artmasına yol açar (Caldwell, 2001). Son zamanlarda yapılan araştırmalar, ergenlere yönelik teorik olarak tasarlanmış programlarda doğada kazanılan etkinlik becerilerinin akademik etkinliğe genellenebileceğini göstermekte, kendine güven alt boyutundaki azalma ise bireylerin korkuyla ilişkili yüksek düzeyde uyarılma (Taniguchi, 2017) yaşamasından kaynaklı olabileceği düşünülmektedir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Bunun sonucunda yeni oluşturulan kodlar, farklı performans becerilerini içerebilir, ancak benzer genel becerilerin kullanımını gerektirebilir. Bir başka söylemle kış şartlarında yaşamı sürdürme becerisini sergileyerek başarılı olan bir bireyin kazanacağı öz-yeterlik, farklı bir beceriye ilişkin yeni belirlenecek kodlara etki edebilir (Taniguchi, 2017). Ya da dağcılık eğitiminde edinilen deneyim eleştirel düşünce ve risk alma eğilimleri üzerinde etki yaratabilir.…”
Section: Introductionunclassified